Renal compression caused by a giant retroperitoneal appendiceal abscess in a child: a rare case report and literature review - He, Yuan-fei; Qi, Shi-qin; Bian, Jian; Zhou, Cheng-xiao; Duan, Yong-peng (Frontiers in Pediatrics, 2025)
ObjectiveTo enhance understanding of the diagnosis and management of retroperitoneal appendiceal abscesses in children.MethodsA retrospective analysis was conducted on the clinical data and surgical approach of a pediatric patient with renal compression caused by a giant retroperitoneal appendiceal abscess, treated in the Department of Pediatric Surgery at our Hospital. A review of the relevant literature was also performed.ResultsAfter confirming the diagnosis of a retroperitoneal appendiceal abscess through comprehensive abdominal examinations, the patient successfully underwent retroperitoneal percutaneous catheter drainage under ultrasound guidance. The procedure lasted 25 min, with approximately 300 ml of pus drained intraoperatively. Post-drainage, the patient's fever and abdominal pain significantly improved. The patient was discharged in good condition after a 12-day postoperative hospital stay, with a recommendation to undergo appendectomy 3 months later.ConclusionThis case provides valuable insight into the diagnosis and surgical management of retroperitoneal appendiceal abscesses in children. For patients presenting with retroperitoneal abscesses, it is crucial to actively investigate appendiceal origin as a potential cause.